The Syllable And Word In Diadochokinetic Javanese - Indonesia Speakers - Hafidz Triantoro Aji Pratomo (Poltekkes Kemenkes Surakarta, 2022)
Background: Diadochokinetic is an activity used to measure individual’s ability of spelling a speech sound, syllable, and word. Age and language is two variables affecting diadochokinetic activity. Although researches have been conducted on some languages to find out diadochokinetic profile, diadochokinetic data in Indonesian is required. This study was conducted to find out the correlation between syllable and word, and phonemic characteristics. Methods: Data was collected by involving skilled enumerator. Data was taken in January 2020. The respondents of research were 100 students in Surakarta City. Diadochokinetic instrument consisted of syllable and world levels composed of one, two, and three syllables. Statistic analysis was carried out using Spearman correlational test and logistic regression. Results: Statistic values for the word with two syllables are mean 3.51; SD: 0.79; CI 95%: 3.35-3.67. Those for the word with one syllable are mean 5.08; SD: 1.31; CI 95%: 4.82-5.34. The repetition time for the word with one syllable is shorter than that with two syllables. Conclusion: The result of statistics shows that there is a mean value of word group. Research area is important to be expanded to measure the broader contextual variation. Researches on diadochokinetic in other age groups need to be done to compare the data yielded.